A ZnCdS / FePO4 composite photocatalytic material, its preparation method and application

CN122937829APending Publication Date: 2026-10-20生态环境部固体废物与化学品管理技术中心
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610706642.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]为了克服现有技术中FePO4材料的光催化性能差的缺陷,本发明提供一种具有优异光催化活性的ZnCdS/FePO4复合光催化材料及其制备方法和应用

Benefits of technology

本发明以废旧磷酸铁锂电池正极提锂后的废渣为原料,通过一步煅烧法获得纳米微球状FePO4。在此基础上,通过水热合成法将ZnCdS原位负载于FePO4表面,形成ZnCdS/FePO4异质结结构。该结构具有较大的比表面积,暴露出更多活性位点。同时,在可见光照射下,ZnCdS产生的光生电子能够快速转移至FePO4表面并与空穴结合,从而有效抑制光生载流子的复合速率。本发明制备的复合材料对诺氟沙星的降解率在1小时内可达到96%以上,远高于单一的FePO4或ZnCdS。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention belongs to the field of water treatment catalytic materials technology, specifically relating to a ZnCdS / FePO4 composite photocatalytic material, its preparation method, and its applications. This invention uses the waste residue from lithium extraction from spent lithium iron phosphate battery cathodes as raw material, which is calcined to obtain nano-spherical FePO4 material. ZnCdS is then in-situ loaded onto the surface of the FePO4 material via hydrothermal synthesis, forming a ZnCdS / FePO4 heterojunction structure. This invention utilizes spent batteries as raw materials, achieving resource utilization; by forming the ZnCdS / FePO4 heterojunction structure, photogenerated carrier recombination is effectively suppressed, significantly improving photocatalytic activity. The degradation rate of norfloxacin by this ZnCdS / FePO4 composite photocatalytic material is much higher than that of FePO4 or ZnCdS alone. The preparation method of this invention is simple and low-cost, and the obtained material has broad application prospects in the photocatalytic degradation of pollutants such as antibiotics and dyes in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment catalytic materials technology, specifically relating to a ZnCdS / FePO4 composite photocatalytic material, its preparation method, and its application. Background Technology

[0002] Norfloxacin (NOR), a common antibiotic, has seen widespread use leading to the release of unmetabolized components into the environment via wastewater discharge, resulting in residues in water bodies and disrupting the ecological balance. Furthermore, norfloxacin in water can inhibit the normal growth and reproduction of aquatic microorganisms, disrupting the lower layers of the food chain. Over time, these residual norfloxacin residues can induce antibiotic resistance in bacteria, threatening human health.

[0003] Currently, the main technologies for treating norfloxacin in water bodies include electrochemical oxidation, Fenton / Fenton-like oxidation, and catalytic wet oxidation. However, due to the stability of the antibiotic's molecular structure and its antibacterial properties, existing degradation technologies generally suffer from low removal efficiency, high toxicity of byproducts, and excessive energy consumption and cost.

[0004] In recent years, the booming development of new energy vehicles has led to a large number of lithium iron phosphate (LFP) batteries facing retirement. To reduce the environmental pollution caused by LFP batteries, the recycling of these used batteries is an urgent problem to be solved. FePO4 material can be obtained by recycling the cathode material of used LFP batteries, and FePO4 material can be used as a photocatalyst for the treatment of norfloxacin in water. However, FePO4 material has poor light absorption capacity, and photogenerated electron-hole pairs easily recombine rapidly, resulting in low photocatalytic efficiency. Summary of the Invention

[0005] To overcome the shortcomings of poor photocatalytic performance of FePO4 materials in the prior art, this invention provides a ZnCdS / FePO4 composite photocatalytic material with excellent photocatalytic activity, its preparation method, and its application.

[0006] This invention uses the waste residue from lithium extraction of spent iron phosphate battery cathodes as raw material, transforming the residue into nano-microsphere FePO4 material. This material is then composited with ZnCdS, allowing ZnCdS to embed into the surface of the nano-microsphere FePO4 material, forming a tightly bound ZnCdS / FePO4 heterojunction structure. This structure possesses a large specific surface area, exposing more active sites. Simultaneously, under visible light irradiation, photogenerated electrons from ZnCdS can rapidly transfer to the FePO4 surface and combine with holes, effectively suppressing the recombination rate of photogenerated carriers. This significantly improves the utilization rate of visible light and the photocatalytic activity of the ZnCdS / FePO4 composite photocatalytic material.

[0007] This invention provides a ZnCdS / FePO4 composite photocatalytic material, wherein the ZnCdS / FePO4 composite photocatalytic material is obtained by calcining the leaching residue of the positive electrode of a waste lithium iron phosphate battery after Li extraction to obtain FePO4 material; then the FePO4 material is combined with ZnCdS, so that ZnCdS is loaded in situ on the surface of the FePO4 material to form a ZnCdS / FePO4 heterojunction structure.

[0008] Preferably, FePO4 material has a nanosphere structure; ZnCdS has an embroidered sphere structure.

[0009] This invention provides a method for preparing a ZnCdS / FePO4 composite photocatalytic material, comprising the following steps: The leaching residue from the positive electrode of a spent lithium iron phosphate battery after Li extraction is calcined to obtain FePO4 material. The FePO4 material, water-soluble zinc salt, water-soluble cadmium salt and sulfur source are dissolved in water and subjected to a hydrothermal reaction to allow ZnCdS to be loaded in situ onto the surface of the FePO4 material, forming a ZnCdS / FePO4 heterojunction structure, thus obtaining a ZnCdS / FePO4 composite photocatalytic material.

[0010] Preferably, the hydrothermal reaction temperature is 140℃; the hydrothermal reaction time is 5h to 8h. If the hydrothermal reaction temperature is too low, the driving force for the hydrothermal reaction will be insufficient, and Zn... 2+ Cd 2+ With S 2- The nucleation and crystallization processes are hindered, preventing ZnCdS from being uniformly and firmly loaded onto the FePO4 material surface. This leads to ZnCdS detachment, poor dispersion, and a large number of free ZnCdS nanoparticles that cannot form a tight heterojunction interface. Excessively high hydrothermal reaction temperatures accelerate ion diffusion and excessive crystal growth, causing abnormal ZnCdS grain growth and sintering agglomeration. This not only blocks the pores of the FePO4 material and significantly reduces the specific surface area but also damages the microstructure of the support, resulting in ZnCdS detaching from the FePO4 material surface and disrupting the heterojunction interface.

[0011] Preferably, the molar ratio of FePO4 material, water-soluble zinc salt, and water-soluble cadmium salt is 1:0.1–0.5:0.1–0.5; the molar ratio of FePO4 material to sulfur source is 1:0.3–1.2. Increasing the Zn content leads to a decrease in the crystallinity of ZnCdS or an increase in surface defects, which in turn hinders the carrier transport efficiency, resulting in a slight decline in photocatalytic performance.

[0012] Preferably, during the preparation of FePO4 material, the calcination temperature is 500℃~700℃ and the calcination time is 3h~7h.

[0013] Preferably, the water-soluble zinc salt is zinc acetate dihydrate, zinc sulfate, zinc nitrate, or zinc chloride; the water-soluble cadmium salt is cadmium acetate dihydrate, cadmium sulfate, cadmium nitrate, or cadmium chloride; and the sulfur source is thiourea, thioacetamide, or sodium sulfide. The water-soluble zinc salt used as a raw material refers to the zinc salt that can dissolve in water and ionize to release Zn. 2+ Compounds; water-soluble cadmium salts refer to compounds that can dissolve in water and ionize to release Cd. 2+ The compound. Its principle lies in the fact that, in the high-temperature, high-pressure environment of a hydrothermal reaction, water serves as the reaction medium, dissolving Zn... 2+ and Cd 2+ S that can decompose with sulfur source 2- A uniform co-precipitation reaction occurs, leading to in-situ nucleation and growth of tightly bound ZnCdS on the FePO4 support surface. The sulfur source refers to the substance that can release sulfur under the reaction conditions. 2- Alternatively, substances that provide sulfur, with thiourea being a preferred sulfur source, slowly hydrolyze to produce sulfur during hydrothermal processes. 2- This helps to control the growth rate of crystal nuclei and avoid the rapid agglomeration of sulfide particles, thereby obtaining a composite structure with uniform coating.

[0014] This invention provides the application of a ZnCdS / FePO4 composite photocatalyst as a photocatalyst in the degradation of norfloxacin.

[0015] Preferably, the application method is as follows: the ZnCdS / FePO4 composite photocatalytic material is mixed with norfloxacin solution, and the photocatalytic degradation of norfloxacin is carried out under the irradiation of a light source.

[0016] Preferably, the solid-liquid ratio of the ZnCdS / FePO4 composite photocatalyst material to the norfloxacin solution is 2 mg to 10 mg: 10 mL; the concentration of the norfloxacin solution is 10 mg / L.

[0017] Compared with the prior art, the present invention has the following technical effects: This invention uses the waste residue from lithium extraction of spent lithium iron phosphate battery cathodes as raw material, and obtains nano-spherical FePO4 through a one-step calcination method. Based on this, ZnCdS is in-situ loaded onto the FePO4 surface via a hydrothermal synthesis method to form a ZnCdS / FePO4 heterojunction structure. This structure has a large specific surface area, exposing more active sites. Simultaneously, under visible light irradiation, photogenerated electrons generated by ZnCdS can rapidly transfer to the FePO4 surface and combine with holes, thereby effectively suppressing the recombination rate of photogenerated carriers. The composite material prepared by this invention achieves a degradation rate of over 96% for norfloxacin within 1 hour, far exceeding that of FePO4 or ZnCdS alone.

[0018] This invention uses the waste residue after lithium extraction from the positive electrode of waste lithium iron phosphate batteries as raw material to prepare FePO4, which not only solves the environmental pollution problem of waste residue, but also realizes high-value conversion and provides a new way for the recycling of waste batteries.

[0019] The preparation method of the present invention is simple, mild, easy to operate, and suitable for large-scale production. Attached Figure Description

[0020] Figure 1 SEM images of the ZnCdS / FePO4 composite photocatalyst prepared in Example 2, the FePO4 photocatalyst prepared in Comparative Example 1, and the ZnCdS photocatalyst prepared in Comparative Example 2 are shown. Specifically, (a) is the SEM image of the ZnCdS photocatalyst prepared in Comparative Example 2; (b) is the SEM image of the FePO4 photocatalyst prepared in Comparative Example 1; and (c) is the SEM image of the ZnCdS / FePO4 composite photocatalyst prepared in Example 2.

[0021] Figure 2 The graph shows a comparison of the degradation rates of norfloxacin by the ZnCdS / FePO4 composite photocatalyst materials prepared in Examples 1 to 4. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention. Unless otherwise specified, all raw materials and reagents used in the following embodiments are commercially available.

[0023] The "li-extracted waste lithium iron phosphate battery cathode leaching residue" used in the following examples comes from the leaching residue obtained by a company from acid leaching of waste lithium iron phosphate battery cathode materials, and this leaching residue is used as the starting material.

[0024] Example 1 A method for preparing a ZnCdS / FePO4 composite photocatalytic material includes the following steps: The leaching residue from the spent lithium iron phosphate battery cathode after Li extraction was transferred to a muffle furnace and calcined at 700℃ for 7 hours with a heating rate of 10℃ / min to obtain a light pink powdery FePO4 material.

[0025] Dissolve 0.3 g of FePO4 material in 40 mL of deionized water, then add 0.0554 g of zinc acetate dihydrate and 0.0672 g of cadmium acetate dihydrate, and sonicate for 20 min until zinc acetate dihydrate and cadmium acetate dihydrate are completely dissolved to obtain a mixed solution.

[0026] Add 0.0480 g of thiourea to 15 mL of deionized water and stir until dissolved to obtain a thiourea solution.

[0027] Thiourea solution was added dropwise to the mixed solution and stirred for 30 min. Then, it was transferred to a high-pressure reactor and kept at 140 °C for 8 h. After cooling to room temperature, it was filtered, and washed three times alternately with deionized water and ethanol. It was then dried at 60 °C for 5 h to obtain the ZnCdS / FePO4 composite photocatalyst material, denoted as 15%ZnCdS / FePO4.

[0028] Example 2 A method for preparing a ZnCdS / FePO4 composite photocatalytic material includes the following steps: The leaching residue from the spent lithium iron phosphate battery cathode after Li extraction was transferred to a muffle furnace and calcined at 700℃ for 7 hours with a heating rate of 10℃ / min to obtain a light pink powdery FePO4 material.

[0029] Dissolve 0.3 g of FePO4 material in 40 mL of deionized water, then add 0.0784 g of zinc acetate dihydrate and 0.0953 g of cadmium acetate dihydrate, and sonicate for 20 min until zinc acetate dihydrate and cadmium acetate dihydrate are completely dissolved to obtain a mixed solution.

[0030] Add 0.0680g of thiourea to 15mL of deionized water and stir until dissolved to obtain a thiourea solution.

[0031] Thiourea solution was added dropwise to the mixed solution and stirred for 30 min. Then, it was transferred to a high-pressure reactor and kept at 140 °C for 8 h. After cooling to room temperature, it was filtered, and washed three times alternately with deionized water and ethanol. It was then dried at 60 °C for 5 h to obtain the ZnCdS / FePO4 composite photocatalyst material, denoted as 20%ZnCdS / FePO4.

[0032] Example 3 A method for preparing a ZnCdS / FePO4 composite photocatalytic material includes the following steps: The leaching residue from the spent lithium iron phosphate battery cathode after Li extraction was transferred to a muffle furnace and calcined at 700℃ for 7 hours with a heating rate of 10℃ / min to obtain a light pink powdery FePO4 material.

[0033] Dissolve 0.3 g of FePO4 material in 40 mL of deionized water, then add 0.1345 g of zinc acetate dihydrate and 0.1633 g of cadmium acetate dihydrate, and sonicate for 20 min until zinc acetate dihydrate and cadmium acetate dihydrate are completely dissolved to obtain a mixed solution.

[0034] Add 0.1166g of thiourea to 15mL of deionized water and stir until dissolved to obtain a thiourea solution.

[0035] Thiourea solution was added dropwise to the mixed solution and stirred for 30 min. Then, it was transferred to a high-pressure reactor and kept at 140 °C for 8 h. After cooling to room temperature, it was filtered, and washed three times alternately with deionized water and ethanol. It was then dried at 60 °C for 5 h to obtain the ZnCdS / FePO4 composite photocatalyst material, denoted as 30%ZnCdS / FePO4.

[0036] Example 4 A method for preparing a ZnCdS / FePO4 composite photocatalytic material includes the following steps: The leaching residue from the spent lithium iron phosphate battery cathode after Li extraction was transferred to a muffle furnace and calcined at 700℃ for 7 hours with a heating rate of 10℃ / min to obtain a light pink powdery FePO4 material.

[0037] Dissolve 0.3 g of FePO4 material in 40 mL of deionized water, then add 0.2092 g of zinc acetate dihydrate and 0.2540 g of cadmium acetate dihydrate, and sonicate for 20 min until zinc acetate dihydrate and cadmium acetate dihydrate are completely dissolved to obtain a mixed solution.

[0038] Add 0.1814 g of thiourea to 15 mL of deionized water and stir until dissolved to obtain a thiourea solution.

[0039] Thiourea solution was added dropwise to the mixed solution and stirred for 30 min. Then, it was transferred to a high-pressure reactor and kept at 140 °C for 8 h. After cooling to room temperature, it was filtered, and washed three times alternately with deionized water and ethanol. It was then dried at 60 °C for 5 h to obtain the ZnCdS / FePO4 composite photocatalyst material, denoted as 40%ZnCdS / FePO4.

[0040] Example 5 A method for preparing a ZnCdS / FePO4 composite photocatalytic material includes the following steps: The leaching residue from the spent lithium iron phosphate battery cathode after Li extraction was transferred to a muffle furnace and calcined at 700℃ for 7 hours with a heating rate of 10℃ / min to obtain a light pink powdery FePO4 material.

[0041] Dissolve 0.3 g of FePO4 material in 40 mL of deionized water, then add 0.0248 g of zinc acetate dihydrate and 0.1167 g of cadmium acetate dihydrate, and sonicate for 20 min until zinc acetate dihydrate and cadmium acetate dihydrate are completely dissolved to obtain a mixed solution.

[0042] Add 0.0845 g of thiourea to 15 mL of deionized water and stir until dissolved to obtain a mixed solution.

[0043] Thiourea solution was added dropwise to the mixed solution and stirred for 30 min. The mixture was then transferred to a high-pressure reactor and kept at 140℃ for 8 h. After cooling to room temperature, the mixture was filtered, and washed three times alternately with deionized water and ethanol. The filtered material was then dried at 60℃ for 5 h to obtain the ZnCdS / FePO4 composite photocatalyst material, denoted as 20%Zn. 0.2 Cd 0.8 S / FePO4.

[0044] Comparative Example 1 A method for preparing FePO4 photocatalytic material includes the following steps: The leaching residue from the spent lithium iron phosphate battery cathode after Li extraction was transferred to a muffle furnace and calcined at 700℃ for 7 hours with a heating rate of 10℃ / min to obtain FePO4 photocatalytic material, denoted as FePO4.

[0045] Comparative Example 2 A method for preparing a ZnCdS photocatalytic material includes the following steps: Dissolve 0.3139 g of zinc acetate dihydrate and 0.3811 g of cadmium acetate dihydrate in 40 mL of deionized water, and sonicate for 20 min until the zinc acetate dihydrate and cadmium acetate dihydrate are completely dissolved to obtain a mixed solution.

[0046] Add 0.2721 g of thiourea to 15 mL of deionized water and stir until dissolved to obtain a thiourea solution.

[0047] Thiourea solution was added dropwise to the mixed solution and stirred for 30 min. Then, it was transferred to a high-pressure reactor and kept at 140 °C for 8 h. After cooling to room temperature, it was filtered by suction, and washed three times alternately with deionized water and ethanol. It was then dried at 60 °C for 5 h to obtain ZnCdS photocatalytic material, denoted as ZnCdS.

[0048] Test 1: The ZnCdS / FePO4 composite photocatalyst prepared in Example 2, the FePO4 photocatalyst prepared in Comparative Example 1, and the ZnCdS photocatalyst prepared in Comparative Example 2 were characterized using field emission scanning electron microscopy (FE-SEM, Sirion 200, Philips). The results are as follows: Figure 1 As shown.

[0049] like Figure 1As shown, the ZnCdS photocatalytic material is embroidered spherical in shape. The FePO4 photocatalytic material has a nano-microsphere structure; in the ZnCdS / FePO4 composite photocatalytic material, the embroidered spherical ZnCdS is fully embedded in the nano-microsphere FePO4, forming a tightly bonded composite structure.

[0050] Test 2: Prepare norfloxacin solution: Transfer 10 mg of norfloxacin to a volumetric flask, add 1 L of deionized water, and sonicate for 10 min until completely dissolved. Measure 50 mL of a 10 mg / L norfloxacin solution into six beakers, and add 10 mg of 15% ZnCdS / FePO4, 20% ZnCdS / FePO4, 30% ZnCdS / FePO4, 40% ZnCdS / FePO4, and 20% ZnCdS / FePO4 solutions respectively. 0.2 Cd 0.8 S / FePO4, FePO4, and ZnCdS were irradiated under a 300W xenon lamp for 1.0 h, with 1 mL collected every 10 min for filtration. The degradation rate of norfloxacin in the filtrate was calculated by liquid chromatography. The results are shown in Table 1 and... Figure 2 As shown.

[0051] Table 1. Degradation rate of norfloxacin by different photocatalytic materials Figure 2 The horizontal axis represents the catalytic time, and the vertical axis represents the degradation rate of norfloxacin. For example... Figure 2 As shown, the degradation efficiency of FePO4 prepared in Comparative Example 1 for norfloxacin was approximately 39.42%; the degradation rate of ZnCdS prepared in Comparative Example 2 for norfloxacin was approximately 53.69%. The ZnCdS / FePO4 composite photocatalyst material prepared in this embodiment of the invention showed significantly better degradation efficiency for norfloxacin than FePO4 and ZnCdS alone. Specifically, 20% Zn... 0.2 Cd 0.8 The degradation rate of S / FePO4 reached 96.48% after 1 hour of light irradiation, demonstrating excellent photocatalytic activity. Its photocatalytic mechanism lies in the 20% Zn... 0.2 Cd 0.8 S / FePO4 has a large specific surface area, which can improve the light absorption rate; at the same time, the heterojunction structure formed by ZnCdS and FePO4 effectively promotes the separation of photogenerated electron-hole pairs, thereby greatly improving the efficiency of photocatalytic reaction.

[0052] In summary, this invention uses the waste residue from lithium extraction of spent lithium iron phosphate batteries as raw material, transforming the residue into nano-spherical FePO4; then, it is composited with ZnCdS to prepare a ZnCdS / FePO4 composite photocatalytic material. This not only solves the problem of resource utilization of spent lithium iron phosphate batteries but also significantly enhances the photocatalytic effect of the ZnCdS / FePO4 composite photocatalytic material. The heterojunction structure formed at the interface between ZnCdS and FePO4 has a large specific surface area, exposing more active sites. Under visible light irradiation, photogenerated electrons from ZnCdS rapidly transfer to the FePO4 surface and combine with holes, thereby reducing the recombination rate of photogenerated carriers and increasing the photocatalytic degradation rate of pollutants such as norfloxacin. Therefore, this invention has high environmental benefits.

[0053] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.

[0054] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If these modifications and variations fall within the scope of equivalents of this invention, then this invention also intends to include these modifications and variations.

Claims

1. A ZnCdS / FePO4 composite photocatalytic material, characterized in that, The ZnCdS / FePO4 composite photocatalytic material is obtained by calcining the leaching residue of the positive electrode of a waste lithium iron phosphate battery after Li extraction to obtain FePO4 material; then, the FePO4 material is combined with ZnCdS, so that ZnCdS is loaded in situ on the surface of the FePO4 material to form a ZnCdS / FePO4 heterojunction structure.

2. The ZnCdS / FePO4 composite photocatalytic material according to claim 1, characterized in that, FePO4 materials have a nano-microsphere structure; ZnCdS has an embroidered sphere structure.

3. A method for preparing the ZnCdS / FePO4 composite photocatalytic material according to claim 1 or 2, characterized in that, Includes the following steps: The leaching residue of the spent lithium iron phosphate battery cathode after Li extraction was calcined to obtain FePO4 material. FePO4 material, water-soluble zinc salt, water-soluble cadmium salt and sulfur source are dissolved in water and subjected to hydrothermal reaction to allow ZnCdS to be loaded in situ onto the surface of FePO4 material, forming a ZnCdS / FePO4 heterojunction structure, thus obtaining a ZnCdS / FePO4 composite photocatalytic material.

4. The preparation method of the ZnCdS / FePO4 composite photocatalytic material according to claim 3, characterized in that, The molar ratio of FePO4 material, water-soluble zinc salt, and water-soluble cadmium salt is 1:0.1-0.5:0.1-0.5; The molar ratio of FePO4 material to sulfur source is 1:0.3 to 1.

2.

5. The preparation method of the ZnCdS / FePO4 composite photocatalytic material according to claim 3, characterized in that, The hydrothermal reaction temperature is 140℃; the hydrothermal reaction time is 5h to 8h.

6. The preparation method of the ZnCdS / FePO4 composite photocatalytic material according to claim 3, characterized in that, In the preparation of FePO4 materials, the calcination temperature is 500℃~700℃ and the calcination time is 3h~7h.

7. The preparation method of the ZnCdS / FePO4 composite photocatalytic material according to claim 3, characterized in that, The water-soluble zinc salts are zinc acetate dihydrate, zinc sulfate, zinc nitrate, or zinc chloride; the water-soluble cadmium salts are cadmium acetate dihydrate, cadmium sulfate, cadmium nitrate, or cadmium chloride; and the sulfur source is thiourea, thioacetamide, or sodium sulfide.

8. The application of a ZnCdS / FePO4 composite photocatalyst as a photocatalyst in the degradation of norfloxacin pollutants, characterized in that, The ZnCdS / FePO4 composite photocatalyst material is the ZnCdS / FePO4 composite photocatalyst material as described in claim 1 or 2.

9. The application of the ZnCdS / FePO4 composite photocatalyst material according to claim 8 as a photocatalyst in the degradation of norfloxacin, characterized in that, The application method is as follows: ZnCdS / FePO4 composite photocatalyst material is mixed with norfloxacin solution, and norfloxacin is photocatalytically degraded under light source irradiation.

10. The application of the ZnCdS / FePO4 composite photocatalyst material according to claim 9 in the degradation of norfloxacin, characterized in that, The solid-liquid ratio of the ZnCdS / FePO4 composite photocatalyst material to the norfloxacin solution is 2 mg to 10 mg: 10 mL; the concentration of the norfloxacin solution is 10 mg / L.